Artful rainwater design : creative ways to manage stormwater - Echols, Stuart, 1961-; Pennypacker, Eliza (2015)
Artful Rainwater Design has three main parts: first, the book outlines five amenity-focused goals that might be highlighted in a project: education, recreation, safety, public relations, and aesthetic appeal. Next, it focuses on techniques for ecologically sustainable stormwater management that complement the amenity goals. Finally, it features diverse case studies that show how designers around the country are implementing principles of artful rainwater design.
The history of stormwater management and background for artful rainwater design -- Achieving amenity with artful rainwater design -- Achieving utility with artful rainwater design -- Case studies of artful rainwater design.
Includes bibliographical references (pages 271-273) and index.
Keywords: Urban runoff -- Management; Water harvesting; Water in landscape architecture; Landscape construction